Deaths During Sport and Recreational Activities in Istanbul. (1st June 2016) - Özdemir, Çaglar; Asil, Hasim; Saka, Tolga; Üzün, Ibrahim; Kar, Hakan
Abstract: Sudden deaths can be simply explained as the rapid loss of heart functions of the individuals and recently an increase in sports-related sudden deaths is observed in forensic practice in Turkey. Reported here are six cases of sports-related sudden deaths to emphasize the pathological mechanisms with optimal screening strategies where a detailed postmortem examination were carried out for all. Except for one case, all cases occurred while playing soccer where coronary artery disease was established as the cause of death in four cases and as arrthymogenic right ventricular dysplasia in the other case. Toxicological analyses revealed 60 ng/ml benzodiazepine concentrations in one case. Sports activities should be undertaken cautiously, particularly in the presence of risk factors. Beside professionals, screening of the recreational athletes is also important. By this way, early diagnosis of most cardiovascular abnormalities can be provided.